Breached Sandbar and Changing Coastal Systems: Interpreted and Perceived Impacts of Flood-Control Interventions at Calido Beach, Sri Lanka - Thulani, HC; Ranaweera, AD; Trafford, Julie; Wickramasinghe, D (Elsevier BV, 2026)
Calido Beach, located on the southwestern coast of Sri Lanka, has experienced substantial environmental and socio-economic change in recent years. These changes have coincided with flood-control interventions implemented in 2017, including partial removal of a sand spit barrier and widening of the Kalu River mouth. However, the extent to which observed changes can be attributed to these interventions remains uncertain due to the inherently dynamic nature of coastal systems. This study integrates qualitative interpretations and comparisons of satellite imagery with community-based survey data to examine environmental transformations and associated livelihood impacts. Google Earth imagery from 2010 to 2024 was analysed to identify broad changes in shoreline configuration, sandbar morphology, and adjacent landforms. In parallel, structured face-to-face surveys were conducted with 70 individuals engaged in fisheries, tourism, small businesses, and sand mining activities to assess perceptions of environmental and socio-economic change. Satellite imagery interpretation indicates substantial modification of the sandbar and associated mangrove cover. Changes include erosion, landward migration, and transformation into lagoonal and vegetated features. Survey results show that 73% of respondents expressed dissatisfaction with flood-control measures, while 40% attributed observed erosion to a combination of natural processes and human interventions. Fisher Exact Tests identified significant associations between perceptions of environmental change and duration of residence, as well as between satisfaction with interventions and income source (p < .001). These relationships should be interpreted cautiously given the small sample size and uneven subgroup distribution. Overall, the findings highlight the importance of integrating community perceptions with scientifically robust coastal analysis. The results support the need for participatory and evidence-based approaches to coastal management, while underscoring the limitations of qualitative geomorphological assessment for establishing causal relationships.
Keywords: 04 Earth Sciences; 05 Environmental Sciences; 16 Studies in Human Society; Fisheries; 37 Earth sciences; 41 Environmental sciences; 44 Human society; Calido beach; Sri Lanka; Coastal erosion; Flood control measures; Community perceptions